974 ASSOCIATION BETWEEN NOTTINGHAM HIP FRACTURE SCORE AND FRAILTY IN ELDERLY ACUTE HIP FRACTURE PATIENTS. (14th June 2022) - Nandi, A; Obiechina, N; Mubin, M; Khan, R; Mukherjee, B
Abstract: Introduction: Nottingham Hip Fracture Score (NHFS) is a well validated risk stratification tool that has been shown to predict 30 day mortality in elderly patients with acute hip fractures. A lot of older patients that sustain hip fractures are frail. The Rockwood Clinical Frailty Scale (CFS) has been validated as a tool to screen for frailty in acutely ill patients and has been shown to predict outcomes in acutely ill elderly patients. The aim of this study was to determine if there is any correlation between the NHFS and CFS in elderly patients with acute hip fractures and to evaluate the effect of gender on this correlation. Method: A retrospective, cross-sectional analysis was carried out on patients admitted with acute hip fractures between January and December 2019 in a single centre trauma and orthopaedic unit. Data was extracted from anonymized electronic patient records. Patients were included if they were 60 years and above; those less than 60 were excluded. Patients with missing data were excluded from analysis. NHFS and CFS were calculated in these patients. SPSS 27 IBM software was used for statistical analysis. Baseline characteristics were calculated using descriptive statistics and spearman's correlation co-efficient and linear regression were used to determine correlation. Results: A total of 268 patients were analysed—65 males and 202 females. Mean age was 83 years (SD 8.5). There was statistically significant positive correlation between NHFS and CFS in all patients, male patients and female patients (r = 0.589; p < 0.001, r = 0.603; p < 0.001, and r = 0.599; p < 0.001 respectively). Conclusion: NHFS is positively correlated with CFS in elderly acute hip fracture patients. Reference(s) Doherty W.J, Stubbs T.A et al. Prediction of Postoperative Outcomes Following Hip Fracture Surgery: Independent Validation and Recalibration of the Nottingham Hip Fracture Score. Journal of the American Medical Directors Association;22(3):663–669.e2.